Acute spontaneous subdural hematoma in infancy due to vitamin K deficiency: Case report - Erol, F.S.; Ozveren, M.F.; Yilmaz, N.; Topsakal, C. (My University, 2000)
The occurence of acute spontaneous subdural hematomas in infancy is rare. The purpose of this report is to present a case of acute spontaneous subdural hematoma due to vitamin K deficiency in infancy. The mechanism of this condition is discussed. The clinical manifestations, diagnosis and treatment of acute spontaneous subdural hematoma due to vitamin K deficiency are reviewed.
K vitamini eksikligine bagli infantil akut spontan subdural hematom: Olgu sunumu
Keywords: Acute subdural hematoma; Vitamin K deficiency